Entity Relationship Diagram (ERD) Learning Courseware / Nur Afiqah Azizan - Azizan, Nur Afiqah (2020)
Entity Relationship Diagram (ERD) Learning Courseware is software designed for educational purposes where the user can used it using CD-ROM. This courseware can help the students and to learn the Entity Relationship Diagram (ERD) topic in interesting way and it also can be used by the lecturer as an educational material to deliver learning content. The solve the current problem that face by the students, The ADDIE model has been used as a guideline in designing and developing of the courseware that consists five phases which are analysis, design, development, implementation, and evaluation. Moreover, the courseware testing and user evaluation has been conducted by developer and users in order to identify the functionality and usability of the courseware. To identify the usability of the courseware, user evaluation is used the ISO (International Organization for Standardization) for usability metrics which includes effectiveness, efficiency, and satisfaction. The user evaluation involved 5 selected students as a user to evaluate the usability of the courseware. As a result from the user evaluation, the effectiveness of the courseware are 83.33% which the courseware are easy to use by the users. Then the result for efficiency can be measure using time-based efficiency and overall relative efficiency while for result of satisfaction are 87.5 which means the users are satisfied with the usability of the courseware. Based on this usability result it can help the developer to improve the courseware. Also, the courseware need to be improve with more interactives, activities and content to improves user in understanding the ERD topic.